Nutritional status of tourists hospitalized with gastrointestinal diseases in Mazatlan, Sinaloa, México - Beltrán – Rodríguez, Paola (2024)
Tourist activity in Mazatlán, Mexico involves various attractions, including the consumption of raw seafood, which leads to a greater risk of infections transmitted by microorganisms, since tourists are unaware of the dangers. The study aims to assess nutritional status and its association with gastrointestinal diseases in tourists hospitalized during the period 2014 - 2018 in Mazatlán Sinaloa. This research is retrospective with a quantitative and cross-sectional approach, based on a non-experimental, descriptive, and correlational design. The technique used was anthropometric and a validated survey of dietary practices for seafood consumption on the clinical records of 96 patients from a private hospital in Mazatlán. Biochemical parameters such as glucose, hemoglobin, cholesterol, and triglycerides were reviewed, and anthropometric parameters of weight and height with BMI calculation. Malnutrition problems include deficiency and excess disorders, as well as imbalances in caloric and nutrient intake, such as malnutrition, overweight, obesity, and chronic non-communicable diseases related to diet are characterized by being conditions associated with poor nutrition. A state of malnutrition can favor the appearance of various complications such as infections due to altered immunity, difficulty in wound healing, hypoproteinemia, alterations in intestinal motility, and musculoskeletal functionality, compared to those who have a normal nutritional status. Of the tourists who were diagnosed with gastroenteritis, 60.41% were malnourished: of which 38.54% were overweight, 19.79% were obese 2.08% were malnourished and only 39.58% of patients had a normal weight, according to the cut-off points of the World Health Organization. In conclusion, 75% of patients with gastroenteritis are international tourists and 25% are domestic tourists. In this study, it was determined that 60.2% of patients suffered from malnutrition (38.5% due to overweight; 19.7% obesity and 2% malnutrition), so this is a risk factor for the development of gastrointestinal diseases, especially in people who travel to other regions during tourist activities.